2020
DOI: 10.1007/s43440-020-00067-5
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-like effects of kynurenic acid in a modified forced swim test

Abstract: Background Kynurenic acid (KYNA) is an l-tryptophan metabolite with neuromodulatory activities, regulating the release of neurotransmitters such as glutamate, dopamine (DA), and acetylcholine (Ach). Dysregulation of the kynurenine pathway has been associated with neurodegenerative, neurological, and psychological disorders such as Alzheimer's disease, Parkinson's disease, Huntington's disease, major depressive disorder, and schizophrenia. Methods The antidepressant-like effects of KYNA were studied with a modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 17 publications
4
51
0
Order By: Relevance
“…Another recent study also suggested that KYNA would be a potential biomarker in diagnosing depression patients 28 . In addition to reduced KYNA levels in MDD, a recent study demonstrated that the administration of KYNA induced antidepressant-like effects in an animal model of depression 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study also suggested that KYNA would be a potential biomarker in diagnosing depression patients 28 . In addition to reduced KYNA levels in MDD, a recent study demonstrated that the administration of KYNA induced antidepressant-like effects in an animal model of depression 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 15 days of supplementation of FO as a source of omega-3 fatty acid to PPD-like rats have successfully reduced their immobility time in FST [ 13 , 17 ]. However, there is paucity of information with regards to the effects of FO on active behaviors, swimming and climbing time in PPD-like rats, as increased swimming time and decreased immobility time in FST is an indicator that the rats being tested are less depressed [ 33 ]. The present study showed that FO significantly increased the swimming time, but decreased the climbing time of the PPD-like rats.…”
Section: Discussionmentioning
confidence: 99%
“…The rs9657182 SNP is linked to moderate or severe IFN-α-induced depressive symptoms in Caucasian patients with chronic hepatitis C. The SNP is located in the linkage disequilibrium block encompassing 20 kilobases upstream of IDO1 as well as includes at least six additional polymorphisms that may contain binding sites for immunoregulatory proteins or may have epigenetic regulatory function [30]. In addition, a downstream metabolite kynurenic acid was found an antidepressant in animal mode of depression [44]. Indoximod is a methylated TRP that inhibits IDO to maintain or elevate TRP levels important to T cell function.…”
Section: Discussionmentioning
confidence: 99%